PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS CONTEXTUAL TEACHING AND LEARNING DENGAN SETTING KOOPERATIF TIPE STAD POKOK BAHASAN TABUNG DAN KERUCUT UNTUK SISWA SMP KELAS IX - Melinda, Tina; Sugiarti, Titik; Pambudi, Didik Sugeng (Department of Mathematics Education , University of Jember, 2015)
Abstract. The research aims to know the process and result of development of mathematics learning materials based on contextual teaching and learning by setting of cooperative learning student team achievement division for cylinder and cone topics at ninth grade of junior high school. Learning instruments development model refers to 4D Thiagarajan models which has 4 steps namely define, design, develop, and disseminate. This research has three products namely lesson plan, worksheet, and evaluation test. Based on validation process and tryout, the result shows that the coefficient of validity reachs 3 point, the percentages of teacher’s activities, students’ activities, and students’ responses are above 80%, it can be concluded that the learning instruments had fullfiled the validity, practice, and effective criteria. Key Words: 4D Thiagarajan models, contextual teaching and learning, cooperative learning student team achievement division, cylinder and cone